Impact of Academic Stress on College Student Anxiety Levels - Zhao, Xue (Transactions on Social Science, Education and Humanities Research, 2024)
Students generally face greater academic stress and college students are no exception. Academic stress among college students has long been of concern to various scholars. In particular, studies in recent years have increasingly indicated that academic stress among college students leads to higher levels of anxiety. Therefore, it is necessary to study the relationship between academic stress and anxiety level of university students. This study focuses on the influence of college students' academic anxiety on their academic achievement. Through this study, we understand the degree of college students' learning anxiety, the factors affecting college students' learning anxiety and the influence of the degree of learning anxiety on college students' academic achievement. And through the analysis of the survey results, we propose some suggestions to alleviate and reduce college students' learning anxiety. Through this study, it can be found that college students of different genders and grades face different AS, among which female college students face more AS, and senior college students are under greater pressure. AS far as the influencing factors are concerned, the external factors mainly include expectation, fierce competition, heavy learning tasks, lack of learning resources, inadequate teachers and facilities, etc. The personal factors of college students mainly include lack of learning motivation and poor academic performance. AS can have a serious impact on the mental health of college students, including anxiety, depression, lower confidence and self-esteem.